When Is a Fish Not a Fish? Questions Raised by a Nage Life-Form Category - Forth, Gregory (Ethnobiology Letters, 2012)
Speakers of a Central-Malayo-Polynesian language, the Nage inhabit the central region of the eastern Indonesian island of Flores. Their folk taxonomy of animals (ana wa) contains three named life-form taxa, one of which is ika, fish. A review of component folk-generic taxa, however, reveals that Nage do not classify five kinds of freshwater fish as ‘fish’ (ika), even though they further apply ika to various marine fish (including sharks and rays) as well as to marine mammals. The article considers this peculiarity of Nage folk zoological taxonomy, and how it might affect an understanding of ika as denoting a ‘fish’ life-form taxon. The main conclusion is that the five excluded categories—distinguished largely on morphological and behavioural grounds, and conveniently designated as the ‘tebhu cluster’, after one of their members—are contrasted primarily with freshwater species which Nage do classify as ‘fish’ (ika). Specified by name as ika lowo (‘river fish’), these are further contrasted with another named folk-intermediate taxon of ‘marine fish’ (ika mesi). From this, it is argued that, as a life-form category, ika should be understood as implicitly including the five members of the ‘tebhu cluster’ as a third, albeit covert, folk-intermediate taxon.